Grade repetition, school drop-out and ineffective school policy - Amiena Bayat; Nontandazo Kohli; siphe madyibi (EDUCATIO : Journal of Education, 2024)
This paper investigates the extent of underperformance, grade repetition and drop-out rates in selected underperforming schools in Amathole West District, Eastern Cape. The findings revealed high failure rates in the selected schools throughout the five years included in the investigation. The findings revealed a high failure rate persisted in the selected schools throughout the five years included in the investigation. Key informants in the study, including teachers and principals, attribute some of the high failure rate to the Promotion and Progression Policy. The chief criticism is that the burden of catching these learners up falls on the teachers while learners exert minimum effort. In addition to the promotion policy and poor resourcing, other in-school and out-of-school factors influence academic performance at the selected schools, such as weak and inconsistent leadership manifested in fluctuating pass rates over the years.